Light up heart-type fatty acid binding protein (FABP3) with a novel fluorine-18 labelled selective FABP3 ligand - Jun Toyohara; Taichi Komoda; Tetsuro Tago; Masahiko Ito; Hiroshi Yoshino (EJNMMI Research)
Abstract Background Heart-type fatty acid binding proteins (FABP3) constitute a family of lipid chaperone proteins. They are found in the cytosol and enhance cellular fatty acid solubilisation, transport, and metabolism. FABP3 is highly expressed in the myocardium and is released from myocytes during myocardial damage. As FABP3 content in the myocardium is closely related to the metabolic state of fatty acids, we hypothesised that targeting of FABP3 with a radiolabelled small organic compound would visualise myocardium. Results The selective FABP3 inhibitor, 4-(4-fluoro-2-(1-phenyl-5-(2-(trifluoromethyl)phenyl)-1H-pyrazol-3-yl)phenoxy)butanoic acid (LUF), was radiolabelled via a two-step reaction comprising copper-mediated 18F-fluorination of an arylboronic precursor followed by alkaline hydrolysis of the ethoxy protecting group. [18F]LUF was successfully synthesised by automated synthesiser with sufficient activity yields (14.0 ± 1.8 GBq) and high quality (molar activity, > 250 GBq/µmol and radiochemical purity, > 99.6%). Biological assessment of [18F]LUF as an in vivo myocardial imaging agent included evaluations of biodistribution, metabolite analysis, and positron emission tomography (PET) imaging of small animals. [18F]LUF clearly visualised the myocardium with high contrast against background tissues such as the lung and liver. [18F]LUF also showed a high absolute myocardial uptake equivalent to that of the promising myocardial perfusion tracer [18F]flurpiridaz and excellent metabolic stability in the body. These properties are ideal for stable and noise-less imaging of the heart. PET imaging of rat surgical permanent myocardial infarction (MI) and experimental autoimmune myocarditis (EAM) was also performed. [18F]LUF successfully visualised lesions of permanent MI and EAM. Conclusion Our results showed for the first time that the 18F-labelled FABP3 selective small organic compound clearly visualised myocardium with good quality. To determine the clinical utility of [18F]LUF for cardiovascular disease in clinical practice, it will be necessary to evaluate a greater variety of cardiovascular disease models and elucidate the accumulation mechanism, particularly in relation to fatty acid metabolism in the myocardium.